2018
DOI: 10.18502/cmm.4.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of antifungal activity of home-generated ozonated Water on Candida albicans

Abstract: Background and Purpose: Candida-associated denture stomatitis is one of the most common forms of oral candidiasis among denture wearers. Regarding this, the aim of the present study was to evaluate the antifungal effects of home-generated ozonated water on the adhesion of the C. albicans attached to the surface of the denture base acrylic resins.Materials and Methods:For the purpose of the study, different concentrations of C. albicans were added to the tubes containing acrylic resin blocks, and then incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Infections caused by Candida species are increasing in immunocompromised patients. Oral candidiasis is one of the most common opportunistic infections in this group of patients (29)(30)(31). The main cause of candidiasis is C. albicans although non-albicans such as C. glabrata and C. krusei are increasing (32).…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by Candida species are increasing in immunocompromised patients. Oral candidiasis is one of the most common opportunistic infections in this group of patients (29)(30)(31). The main cause of candidiasis is C. albicans although non-albicans such as C. glabrata and C. krusei are increasing (32).…”
Section: Discussionmentioning
confidence: 99%
“…These devices are available, relatively cheap, and easy to use and require no special training. In a recent study, the anti-fungal efficacy of this device was tested, and the results revealed that with enough exposure time (80 minutes), the colony count drops significantly [20]. The data regarding the effect of ozonated water on the mechanical properties of denture soft lining materials are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Topical government of PG is required to contribute to the healing of ulcers. About 5% potassium permanganate solution and ozonated water have been reported as effective treatment methods for certain types of wounds . We had no idea why the lesion was in progress before he came to us, although with prednisolone over 1 mg/kg/d for more than 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…About 5% potassium permanganate solution and ozonated water have been reported as effective treatment methods for certain types of wounds. 11,12 We had no idea why the lesion was in progress before he came to us, although with prednisolone over 1 mg/kg/d for more than 1 month. We considered that besides systemic treatment, we actually strengthened measures for wound care.…”
Section: Discussionmentioning
confidence: 99%